2003
DOI: 10.1523/jneurosci.23-16-06596.2003
|View full text |Cite
|
Sign up to set email alerts
|

Functional Connectivity between the Superficial and Deeper Layers of the Superior Colliculus: An Anatomical Substrate for Sensorimotor Integration

Abstract: The superior colliculus (SC) transforms both visual and nonvisual sensory signals into motor commands that control orienting behavior. Although the afferent and efferent connections of this midbrain nucleus have been well characterized, little is know about the intrinsic circuitry involved in sensorimotor integration. Transmission of visual signals from the superficial (sSC) to the deeper layers (dSC) of the SC has been implicated in both the triggering of orienting movements and the activity-dependent process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
43
0
1

Year Published

2004
2004
2009
2009

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 56 publications
5
43
0
1
Order By: Relevance
“…D, Prey capture performance in a bilateral MeLc and MeLr ablated group (a separate group from that presented in C) and control ablated group in which an equal number of identified RS neurons from within hindbrain rhombomeres 4 -6 were ablated. The control ablated group captured significantly more paramecia than the bilateral MeLc and MeLr group across the 5 h assay period and was indistinguishable from the unablated group in C. confirms previous electrophysiological and lesioning studies in other vertebrates (Ewert et al, 2001;Lomber et al, 2001;Doubell et al, 2003). For instance, in trout, activation of the tectum elicits orienting movements, the direction and amplitude of which depend on the site of stimulation (Herrero et al, 1998b).…”
Section: Discussionsupporting
confidence: 85%
“…D, Prey capture performance in a bilateral MeLc and MeLr ablated group (a separate group from that presented in C) and control ablated group in which an equal number of identified RS neurons from within hindbrain rhombomeres 4 -6 were ablated. The control ablated group captured significantly more paramecia than the bilateral MeLc and MeLr group across the 5 h assay period and was indistinguishable from the unablated group in C. confirms previous electrophysiological and lesioning studies in other vertebrates (Ewert et al, 2001;Lomber et al, 2001;Doubell et al, 2003). For instance, in trout, activation of the tectum elicits orienting movements, the direction and amplitude of which depend on the site of stimulation (Herrero et al, 1998b).…”
Section: Discussionsupporting
confidence: 85%
“…Convergence within the oculomotor system seems to be appropriately regarded as occurring at the interface between sensory and motor processing. In this case, it is probably not useful to attempt to categorize the "locus" of summation as occurring at either a sensory or motor stage, since physiological studies have identified neurons within the superior colliculus that have multimodal receptive fields (Bell, Meredith, Van Opstal, & Munoz, 2005;Doubell, Skaliora, Baron, & King, 2003;Dräger & Hubel, 1975a, 1975bFort, Delpuech, Pernier, & Giard, 2002;Joassin, Maurage, Bruyer, Crommelinck, & Campanella, 2004;L. M. Miller & D'Esposito, 2005;Schneider & Kastner, 2005;Sparks, 1986;Stein & Meredith, 1993;Toldi, Fehér, & Wolff, 1986;; reviewed in Isa & Sasaki, 2002; but see Populin & Yin, 2002) and also generate a premotor discharge prior to specific trajectories of saccadic eye movements (e.g., Jay & Sparks, 1984;Meredith & Stein, 1986a;Patton, Belkacem-Boussaid, & Anastasio, 2002;Stein, 1978;Stein & Arigbede, 1972).…”
Section: Location Of Multimodal Convergencementioning
confidence: 99%
“…Coronal slices of the midbrain (500 m) from 26 Sprague-Dawley rats aged P11 to P17 were prepared as described previously (Doubell et al 2000(Doubell et al , 2003. All procedures involving animals were approved and licensed by the United Kingdom Home Office following local ethical committee review.…”
Section: In Vitro Electrophysiologymentioning
confidence: 99%
“…Second, partial aspiration of the sSC in neonatal ferrets impairs the emergence of auditory topography in the region of the dSC underlying the aspirated sSC (King et al 1998b). This can be explained by loss of the topographically organized input from the sSC to the dSC (Behan and Appell 1992;Doubell et al 2003), although the presence of a projection from the sSC to the nBIC (Doubell et al 2000) leaves open the possibility that visual signals could shape auditory responses at an earlier level of the pathway. These results do indicate, however, that the topographic visual signals necessary for refinement of the auditory representation are projected through the sSC.…”
Section: Introductionmentioning
confidence: 99%